Development of Biodegradable Food Packaging Incorporated with Pigment of Rose and Red Cabbage - Maqsood-ul-Haque, Suzihaque; Md Shariffuddin, Nor Syazwani (International Journal of Integrated Engineering, 2022)
Food packaging is essential for maintaining the quality and safety of food. Excessive food packaging made out of plastics could be harmful to the environment. Plastic food packaging takes a long period of time to biodegrade while most of them do not biodegrade and are harmful to the environment. In order to improve the properties of packaging and extend the shelf-life of packaged food, development of biodegradable food packaging is implemented by using natural and renewable resources for the main materials such as extracts from plants due to its ability to decompose and biodegrade in a short time. In this case, biodegradable polymers and films are needed to reduce the external influence of environment such as oxygen and moisture. In this paper, the usage of red cabbage and rose as pH indicator was introduced through extractions using solvents of ethanol and water. The production of film for packaging incorporates starch and chitosan solution and were compared with commercial packaging. Each of the samples or rose and red cabbage were used for the preparation of film by using hot press method. This paper will examine the results of chemical properties such as interaction in the mixture by using FTIR and biodegradability of the film, mechanical properties like tensile strength, and physical properties like pH, colour and the thickness of the film. Commercial packaging gave a better result in term of tensile strength and biodegradability. It also showed that rose is better than red cabbage in terms of preventing food spoilage.  The FTIR results for all samples were quite similar as all the peaks fall into a single bond region.